A Semi-supervised Approach for Opinion Mining using Online Product Review - G. Bhongade, Bhagyashree; V.Z, Ashwini (International Journal of Engineering and Technology, 2018)
The growth of the internet as a secure online shopping channel has developed since 1994. With the Increasing number of e-commerce portal, we are now heavily inclined to online shopping. One of the benefits of online shopping is the ability to read reviews about the product purchased. This paper presents a semi-supervised approach for opinion mining using online product reviews obtained from   Amazon website. A semi-supervised model regards identifying opinion relation as an alignment process and gives more precision in comparison to unsupervised model. Opinion mining of online reviews is needed for first-hand assessments of product information and direct supervision of their purchase actions. Manufacturers can obtain immediate feedback and opportunities to improve the quality of their products in a timely fashion.